2013
DOI: 10.1177/1096348012471384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Loyalty Constructs Among Hotel Reward Program Members Using eWom

Abstract: Electronic word-of-mouth has become a driving force for hospitality businesses. Achieving customer loyalty is a primary goal of hospitality businesses, and reward programs are one mechanism for doing so. Customer-based communication channels have the potential to undermine or support these efforts. This study investigated attitudes toward hotel loyalty programs among members of flyertalk.com, a forum for frequent travelers. A content analysis of 1,519 comments from members of five major hotel programs was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 68 publications
1
61
0
Order By: Relevance
“…Loyalty programs play important roles in customer retention in many industries, including hotel chains, airlines, retail stores, and fi nancial institutions (Berezan, Raab, Tanford & Kim 2013;Han & Ryu 2009;Meyer-Waarden 2008;Tanford, Raab & Kim 2010). The perceived value that the customers attached to their experience with loyalty program such as what the program provides or does for members is reffered to as program benefi ts (Holbrook & Hirschman 1982;Kim, Lee, Choi, Wu & Johnson 2013;Mimouni-Chaabane & Volle 2010).…”
Section: Literature Review Loyalty Program Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loyalty programs play important roles in customer retention in many industries, including hotel chains, airlines, retail stores, and fi nancial institutions (Berezan, Raab, Tanford & Kim 2013;Han & Ryu 2009;Meyer-Waarden 2008;Tanford, Raab & Kim 2010). The perceived value that the customers attached to their experience with loyalty program such as what the program provides or does for members is reffered to as program benefi ts (Holbrook & Hirschman 1982;Kim, Lee, Choi, Wu & Johnson 2013;Mimouni-Chaabane & Volle 2010).…”
Section: Literature Review Loyalty Program Benefitsmentioning
confidence: 99%
“…While program benefi t has been commonly associated with monetary benefi ts which is also known as economic, utilitarian or fi nancial benefi ts (Kreis & Mafael 2014;Mägi 2003;Peterson 1995), other types of benefi ts have been increasingly presented in the loyalty program literature. Steyn et al (2010) classifi ed program benefi ts into two categories, namely fi nancial and information; Berezan et al (2013), in their study of hotel loyalty program classifi ed program benefi ts into standard benefi ts, elite benefi ts, promotion benefi ts, and dilution of elite status benefi ts; Leenheer;Van Heerde, Bijmolt, and Smidts (2007) and Zhang and Breugelmans (2012) categorised program benefi ts into economic, psychological, and sociological; Evanschitzky et al (2011) investigated program benefi ts in terms of social benefi ts, special treatment, and overall program value; Suh and Yi (2012) studied in terms of hedonic and utilitarian benefi ts; and Dorotic, Bijmolt and Verhoef (2012) and Mimouni-Chaabane and Volle (2010) examined it in terms of utilitarian benefits, hedonic benefi ts, and symbolic benefi ts. A recent study done by Terblanche (2014) in the context of airlines industry, conceived that program benefi ts are consisted of convenience, exploration, and recognition.…”
Section: Literature Review Loyalty Program Benefitsmentioning
confidence: 99%
“…Loyalty programs are effective in making customers feel special, important, and appreciated by rewarding them with preferential incentives (Lewis, 2004). Considering that loyalty programs have become popular in the marketplace, their roles are considerably examined in the hospitality literature (e.g., Berezan et al, 2015;Hu et al, 2010;Mattila, 2006;McCall and Voorhees, 2010;Shoemaker and Lewis, 1999;Tanford, 2013). The previous literature have examined the concepts of reward timing, membership tiers, reward program value, commitment, switching costs, and company loyalty to understand the impact of reward programs.…”
Section: Introductionmentioning
confidence: 99%
“…Frustration -By definition, consumer frustration is a highly negative emotion that can be attributed to interference with a potentially satisfying sequence of acts or behaviors (Berezan et al, 2015;Stauss et al, 2005). The notion of frustration is quite relevant to the context of service relationship management.…”
Section: Customer Delight Frustration and Satisfactionmentioning
confidence: 99%
“…The notion of frustration is quite relevant to the context of service relationship management. Of particular relevance to this research is the work of Berezan et al (2015) who discuss consumer frustration with loyalty rewards programs. Based on a content analysis of 1519 comments from members of five major hotel rewards programs, Berezan et al (2015) found that managing customer frustration is paramount.…”
Section: Customer Delight Frustration and Satisfactionmentioning
confidence: 99%